PENGARUH KOMITMEN ORGANISASI, KOMPETENSI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (STUDI PADA DINAS PENDAPATAN DAN PENGELOLAAN ASET DAERAH PROVINSI JAWA TENGAH) (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aims to examine the influence of organizational commitment and competence on employee’s performance through job satisfaction and organizational citizenship behavior (OCB) mediation in Dinas Pendapatan dan Pengelolaan Aset Daerah, Central Java Province.The method used in this study was census, whereas statistic technique was using instrument test with validity test criteria with KMO>0.5 and matrix component >0.4, reliability test with cronbach alpha > 0.7, and multiple regression analysis with adjusted-R square criterion, F test, t-test and path analysis.Based on the results of the study can be summarized as follows: 1) organizational commitment has positive influence on job satisfaction. 2) Competency has positive influence on job satisfaction. 3) Organizational commitment has positive influence on Organizational Citizenship Behavior (OCB). 4) Competency has positive influence on Organizational Citizenship Behavior (OCB). 5) Job satisfaction has positive influence on Organizational Citizenship Behavior (OCB). 6) Organizational commitment has positive influence on performance. 7) Competency has positive influence on performance. 8) Job satisfaction has positive influence on performance. 9) Organizational Citizenship Behavior (OCB) has positive influence on performance.Keywords: Organizational Commitment, Competency, Job Satisfaction, Organizational Citizenship Behavior, Performance